2018
DOI: 10.1182/blood-2017-12-815548
|View full text |Cite
|
Sign up to set email alerts
|

Murine pre–B-cell ALL induces T-cell dysfunction not fully reversed by introduction of a chimeric antigen receptor

Abstract: Adoptive transfer of patient-derived T cells modified to express chimeric antigen receptors (CARTs) has demonstrated dramatic success in relapsed/refractory pre-B-cell acute lymphoblastic leukemia (ALL), but response and durability of remission requires exponential CART expansion and persistence. Tumors are known to affect T-cell function, but this has not been well studied in ALL and in the context of chimeric antigen receptor (CAR) expression. Using TCF3/PBX1 and MLL-AF4-driven murine ALL models, we assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Here, we examined the role of granule-mediated cytotoxicity in CAR T cell responses and toxicity by evaluating the function of perforin-deficient CAR T cells in a syngeneic murine model of anti-CD19 CAR T cell therapy against pre-B cell acute lymphoblastic leukemia (pre-B ALL) (23)(24)(25)(26). We found that perforin was not required for leukemia clearance by CAR T cells but was critical for CAR T cell cytotoxic potency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we examined the role of granule-mediated cytotoxicity in CAR T cell responses and toxicity by evaluating the function of perforin-deficient CAR T cells in a syngeneic murine model of anti-CD19 CAR T cell therapy against pre-B cell acute lymphoblastic leukemia (pre-B ALL) (23)(24)(25)(26). We found that perforin was not required for leukemia clearance by CAR T cells but was critical for CAR T cell cytotoxic potency.…”
Section: Resultsmentioning
confidence: 99%
“…The need for perforin-deficient donor T cells to model HLH-like toxicities may reflect a limitation of the syngeneic murine model using mice in a stardard clean facility: the vast majority of nonmodified T cells in laboratory mice are naive and their myeloid cells are less activated (67), which does not mimic a human who has been exposed to numerous antigens (67)(68)(69). Patients with multiply relapsed leukemia also have been exposed to numerous chemotherapies, corticosteroids, and other immunosuppressants, and their T cells are probably dysfunctional (25). We hypothesize that perforindeficient CAR T cells with a decreased ability to control leukemia at early time points may more accurately reflect the human CAR T cells derived from patients who have suboptimal T cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The low mutation burden and poor antigen presentation capacity of ALL blasts, in concert with a rapid induction of T cell dysfunction by progressive leukemia may contribute to the failure of immune therapy in many ALL patients [22,24,28,29,38]. Our results indicate that TLR agonists, in particular CpG ODN, can exert sufficient immunomodulatory activity to overcome these inhibitory mechanisms to eliminate primary B-ALL cells in the absence of a strong rejection antigen.…”
Section: Discussionmentioning
confidence: 80%
“…CAR T cells from complete-responding patients with CLL were enriched in memory-related genes, including IL-6/STAT3 signatures, whereas T cells from non-responders upregulated programs involved in effector differentiation, glycolysis, exhaustion and apoptosis. T cells from leukemia-bearing mice presented increased expression of inhibitory co-receptors including programmed cell death protein 1 (PD1), Tim3 and LAG3, and introduction of a CAR into these T cells failed to fully reverse poor in vivo function [11]. However, T cells from a haplo-source of healthy donor were not affected by leukemia before infusion and may express lower levels of the inhibitory molecules than T cells from the lymphoma patient.…”
Section: Discussionmentioning
confidence: 99%